Empirical analysis on correlation between housing prices and educatinal performance - Kim, Yoonsan (KDI School, 2011)
The purpose of the study is to analyze the correlation between hosing prices and educational performance, and to specifically interpret the correlation as a nationwide matter. This study, therefore, focuses on Daegu Metropolitan City, a region excluding the Seoul Metropolitan Area where precedent researches were made already. Meanwhile, this study employed the hedonic pricing model being widely used in related academic and practical fields. With that model, two research hypotheses are developed as follows: first, the educational performance in this city influences the condominium prices linearly or nonlinearly; second, the influence changes by lapse of time. To clarify the influence in depth, multifarious analyses are attempted so that Chapter 4 provides a variety of analyses composed of an OLS regression, a time-series analysis, a dummy-variable regression and a panel data analysis. Through these analyses, several key findings are obtained as in the following: 1) the price of a condominium of which the lot size is thirty pyeongs (one hundred square meters) goes up by approximately KRW 13.6 million as of 2009 in terms of the statistic-economics, when an adjacent high school has one more student admitted into the Seoul National University; 2) the magnitude of the influence has increased by average 18.5 percent per annum for five years from 2005 to 2009; 3) the condominium price and the educational performance holds a nonlinear correlation so that, if a student who gains the admission into the Seoul National University belongs to a high school which sends more than ii seven students to the top-class university, the condominium price gets almost doubled; 4) lastly, through the panel data analysis, this study identifies the facts that the influence of unobservable omitted variables is not critical and the most decisive factor by which determines the value of residential real estate in Daegu Metropolitan city is the educational performance.
Thesis(Master) --KDI School:Master of Public Policy,2011